In search of citizen engagement: PSM and Culture in Andalusia and Catalonia - Costa Gálvez, Lola; Hoyos López, Gloria (My University, 2016)
Culture is one of the strongholds of public service broadcasting, and in times of crisis has become a survival guarantee for public media. In Spain, the implementation of public service media strategies has ideally left behind the theory stage and innovative initiatives have been clearly embedded by society. Within this context our research aim is to approach one specific issue faced by two of the Spanish audiovisual corporations: How is culture considered as an asset or strategy to citizen engagement in PSM initiatives of Andalusian (RTVA) and Catalan (CCMA) Spanish regional corporations? Both corporations have received high academic attention; share a similar historical background (including reorganisation procedures concerning culture), comparable staff characteristics, and high audience shares. With a methodology based on in-depth interviews, results show how the marriage of culture and the digital as a tool for engagement is not a main concern for both public corporations.
Keywords: Medios de comunicación social; Public media; Public service; Citizen engagement; Culture; Innovation